Insulin signaling regulates longevity through protein phosphorylation in Caenorhabditis elegans - Li, Wen-Jun; Wang, Chen-Wei; Tao, Li; Yan, Yong-Hong; Zhang, Mei-Jun; Liu, Ze-Xian; Li, Yu-Xin; Zhao, Han-Qing; Li, Xue-Mei; He, Xian-Dong; Xue, Yu; Dong, Meng-Qiu (Nature communications, 2021)
Insulin/IGF-1 Signaling (IIS) is known to constrain longevity by inhibiting the transcription factor FOXO. How phosphorylation mediated by IIS kinases regulates lifespan beyond FOXO remains unclear. Here, we profile IIS-dependent phosphorylation changes in a large-scale quantitative phosphoproteomic analysis of wild-type and three IIS mutant Caenorhabditis elegans strains. We quantify more than 15,000 phosphosites and find that 476 of these are differentially phosphorylated in the long-lived daf-2/insulin receptor mutant. We develop a machine learning-based method to prioritize 25 potential lifespan-related phosphosites. We perform validations to show that AKT-1 pT492 inhibits DAF-16/FOXO and compensates the loss of daf-2 function, that EIF-2α pS49 potently inhibits protein synthesis and daf-2 longevity, and that reduced phosphorylation of multiple germline proteins apparently transmits reduced DAF-2 signaling to the soma. In addition, an analysis of kinases with enriched substrates detects that casein kinase 2 (CK2) subunits negatively regulate lifespan. Our study reveals detailed functional insights into longevity. How phosphorylation mediated by Insulin/IGF-1 Signaling kinases regulates lifespan remains unclear. Here the authors perform a large-scale quantitative phosphoproteomic analysis of wildtype and IIS mutant C. elegans strains to reveal detailed functional insights into longevity.